(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the effectiveness of a management model for pregnant women receiving prophylactic treatment for preeclampsia and to identify factors associated with the effectiveness of this model at Can Tho city Gynecology and Obstetrics Hospital. Methods: A prospective cross-sectional study was conducted on 109 pregnant women identified as high risk for preeclampsia (> 1/100) at 11-13 weeks 6 and days of gestation. Participants were managed and received prophylactic treatment with Aspirin at Can Tho city Gynecology and Obstetrics Hospital from November 2023 to April 2025. Data on treatment adherence, maternal and neonatal outcomes were collected. Model effectiveness was assessed based on pregnancy outcomes, and associated factors were analyzed using logistic regression. Results: The rate of adherence to Aspirin use according to recommended guidelines was 92.7%. The incidence of preeclampsia was 12.8%, with no cases of severe preeclampsia observed. Most pregnancies resulted in term delivery (87.2%), and neonatal outcomes were favorable, with 98.2% of newborns in good condition at birth. The management model achieved a success rate of 82.6%. Multivariate analysis showed that maternal age under 35 years was independently associated with successful model outcomes (OR = 3.258; 95% CI: 1.010-10.514; p = 0.048). Conclusions: The management model incorporating prophylactic Aspirin intervention demonstrated positive effectiveness in improving pregnancy outcomes among high-risk women (82.6%). Maternal age under 35 years was associated with successful model outcomes.